Desempenho térmico e mecânico de alvenaria de adobe ativado alcalinamente e reforçado com fibra de sisal - Pinto, Bruno Ramalho (2021)
The construction with adobes is one of those with the lowest environmental impact on Planet Earth. But “modern” uses of adobes, or earthen construction in general, request stabilization with lime or Portland cement to improve its properties. In this work, another possibility is presented, which is the stabilization of the earth by an "alkaline binder", which also uses impacting chemicals, but in a very small amount only 2.2% of soil mass. Its potential has already been shown in previous works at UFPB, some compositions in certain types of soil even make adobe resistant to water action, with only 1% of the alkaline binder to the earth's mass. Now it is intended to further improve the properties of the blocks with the introduction of sisal fibers, capable of increasing their flexion strength and giving them ductility. The composition of the alkaline binder used involves metakaolin as a precursor and sodium silicate plus calcium hydroxide as activators. Mechanical compressive strengths of the reference and alkaline activated adobe bricks were obtained, with and without sisal fiber. As there is no information on the thermal properties of this product, a test was carried out on 1.0 m x 1.0 m walls in a chamber developed for this purpose, allowing to study the performance of fiber-reinforced adobes in masonry. After thermal tests were finished, walls were tested under compression to understand their structure behavior. The sisal fiber allowed a significant increase in deformation of blocks and adobe wall without loss of strength. Concerning the thermal scope, the presence of sisal decreased the temperature on the cold face of the wall.